Assessing differences among elasmobranch nurseries to aid conservation based on a genomics framework - Dominic G. Swift; Amanda M. Barker; William B. Driggers; Bryan S. Frazier; Douglas H. Adams; James J. Gelsleichter; Dana M. Bethea; Bethany M. Deacy; David S. Portnoy (Conservation Biology, 2026)
Elasmobranch nurseries often differ in environmental conditions, demographics, and use patterns. These differences affect the distribution of genetic variation among nurseries. However, conservation and management strategies often fail to account for such differences because they are difficult to characterize. We assessed differences in connectivity, genetic variation, and numbers of breeders among scalloped hammerheads ( Sphyrna lewini ) sampled in five nurseries in the western North Atlantic Ocean. We used a reduced‐representation genomic approach to genotype 472 young of the year and small juveniles at 8,334 loci containing single‐nucleotide polymorphisms. We inferred full‐ and half‐sibling relationships and used mitochondrial genome haplotypes to differentiate between maternally and paternally related half‐siblings. Among 45 sibling pairs detected, 91% were from the same nurseries and only four pairs were sampled in different nurseries, indicating strong site fidelity. Weak but significant genetic heterogeneity was detected among nurseries based on analysis of molecular variance (0.02% variation, F ST 0.00018, 95% confidence interval 0.00008–0.00028). We quantified standing genetic variation and estimated the contemporary effective population size for each nursery, and although some differences were observed, they were not statistically significant. Our results suggested that female scalloped hammerheads consistently used specific nurseries and that connectivity (via males or females straying between nurseries) facilitated the dispersal of genetic variation, which may enhance population resilience to environmental change. The genomics framework we applied is broadly applicable to conservation‐based assessments of elasmobranch nurseries and essential habitats of other highly mobile species and provides a powerful tool for addressing conservation challenges.

Clinical observations of tetanus toxin plus decoy, Snoretox-1, a novel targeted neuromuscular stimulant, in a pilot study of 6 British bulldogs with BOAS - Anthony Sasse; Luke J. Norbury; Thomas McLean; Maurice Newport; Arthur House; David W. Swift; Danny Aliano; Peter M. Smooker; Russell Conduit (The Veterinary Journal, 2026)

Nest site and habitat changes over 15 years in a predicted climate refugium in Beluga, AK, USA, have a positive impact on Hudsonian godwit (Limosa haemastica) nest survival - Eden Smith; Rose J. Swift; Anna Courtemanche; Feipeng Huang; Mary Margaret Pelton; Lauren Puleo; Josiah Simmons; Matthew M. Waller; Hannah Walton; Casey Weissburg; Luke R. Wilde; Nathan R. Senner (Polar Biology, 2026)

Inventory and Assessment of Wisconsin's Baraboo Hills Country (USA) as an Aspiring UNESCO Global Geopark - Troy P. Swift; Lisa M. Kennedy (Geoheritage, 2025)
We analyzed the Baraboo Hills in south-central Wisconsin (USA) as a first step in consideration of its potential for UNESCO Global Geopark designation. Well over 200 Geoparks exist around the globe; presently none are in the USA. The basis for designation is a geographical area that contains geological heritage of international significance, but a Geopark’s fuller mission according to UNESCO is to “explore, develop and celebrate the links between that geological heritage and all other aspects of the area’s natural, cultural, and intangible heritages.” The Baraboo Hills, bisected by the boundary between glaciated and unglaciated landscapes, offer a surprising level of geodiversity with dramatic peaks, canyons, cliffs, waterfalls, and massive exposures of the somewhat rare and certainly ancient Baraboo quartzite. The Hills, with a broad array of land managers on public and privately owned land, have already garnered national designations. We followed a published approach that combined qualitative and quantitative methods to inventory and assess 62 sites within the region for their scientific, educational, and touristic merit, along with degradation risk. We expanded on that method in two significant ways. First, we combined those four established metrics into a meaningful summary metric (Importance) to improve intra-site comparisons. We also applied geospatial modeling (Kernel Density Surface) across the study area to examine spatial relationships in our data and to determine a perimeter to encompass the area that would benefit from unified protection—a strategy that could enhance future Geopark proposals. This research highlights the significant geological heritage of the Baraboo Hills and documents the region’s potential for Geopark designation.

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

Viral Nervous Necrosis due to Betanodavirus: A Case Study in Pot‐Bellied Seahorses ( Hippocampus abdominals ) - Stephen M. Pefanis; Graeme Knowles; Peter G. Mohr; Kate Swift; Jemma Bergfeld; Teresa K. Wilson; Marianne Douglas; Rachelle Hawkins; John Hoad; Adam Costin; Jacqueline Morris; David Cummins; et al. (Journal of Fish Diseases, 2025)
Betanodaviruses, members of the Nodaviridae family, are the causative agents of viral nervous necrosis in fish, resulting in great economic losses worldwide. This is the first case study describing the detection and confirmation of viral nervous necrosis in pot‐bellied seahorses ( Hippocampus abdominalis ) in Australia. Clinical signs of this infection in the seahorses included whirling, floating and cessation of feeding. Histopathological findings included prominent vacuolation in the grey matter of the brain and in the retina of the eye. Betanodavirus infection was initially detected by betanodavirus reverse transcriptase quantitative PCR and nested PCR. Sequencing confirmed the red‐spotted grouper nervous necrosis virus (RGNNV) genotype of betanodavirus. The RGNNV genotype of betanodavirus has previously been detected in Australia in fish, including barramundi ( Lates calcarifer ) and striped trumpeter ( Latris lineata ). Immunohistochemistry using antibodies directed against the capsid protein of betanodavirus demonstrated intralesional virus antigen. Betanodavirus targeted the brain, spinal cord and retina, causing intracytoplasmic vacuolation of neuronal processes and neuronal necrosis.

The impact of fleet electrification on productivity in heat-constrained underground mines - John Ayaburi; Aaron Swift; Jason M. Porter; Andrea Brickey; Alexandra M. Newman (Journal of Cleaner Production, 2025)

Drought stress homogenizes maize growth responses to diverse natural soil microbiomes - Joel F. Swift; Matthew R. Kolp; Amanda Carmichael; Natalie E. Ford; Paige M. Hansen; Benjamin A. Sikes; Manuel Kleiner; Maggie R. Wagner (Plant and Soil, 2025)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Evaluation of an experimental kelp farm’s structural behavior using regression modelling and response amplitude operators derived from in situ measurements - Zachary Moscicki; M. Robinson Swift; Tobias Dewhurst; Michael MacNicoll; David W. Fredriksson; Michael Chambers; Igor Tsukrov (Ocean Engineering, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

The mismatch between swimming speeds and flow regimes when optimising exercise regimes to improve Chinook salmon, Oncorhynchus tshawytscha, performance - Leteisha A. Prescott; Jane E. Symonds; Seumas P. Walker; Matthew R. Miller; Luke Swift; Neill A. Herbert; Jayson M. Semmens; Chris G. Carter (Aquaculture, 2024)

Design, deployment, and operation of an experimental offshore seaweed cultivation structure - Zachary Moscicki; M. Robinson Swift; Tobias Dewhurst; Michael MacNicoll; Michael Chambers; Igor Tsukrov; David W. Fredriksson; Peter Lynn; Melissa E. Landon; Beth Zotter; Noah MacAdam (Aquacultural Engineering, 2024)

Philopatry influences the genetic population structure of the blacktip shark ( Carcharhinus limbatus ) at multiple spatial scales - Dominic G. Swift; Shannon J. O'Leary; R. Dean Grubbs; Bryan S. Frazier; Andrew T. Fields; Jayne M. Gardiner; J. Marcus Drymon; Dana M. Bethea; Tonya R. Wiley; David S. Portnoy (Molecular Ecology, 2023)
Understanding how interactions among microevolutionary forces generate genetic population structure of exploited species is vital to the implementation of management policies that facilitate persistence. Philopatry displayed by many coastal shark species can impact gene flow and facilitate selection, and has direct implications for the spatial scales of management. Here, genetic structure of the blacktip shark ( Carcharhinus limbatus ) was examined using a mixed‐marker approach employing mitochondrial control region sequences and 4339 SNP‐containing loci generated using ddRAD‐Seq. Genetic variation was assessed among young‐of‐the‐year sampled in 11 sites in waters of the United States in the western North Atlantic Ocean, including the Gulf of Mexico. Spatial and environmental analyses detected 68 nuclear loci putatively under selection, enabling separate assessments of neutral and adaptive genetic structure. Both mitochondrial and neutral SNP data indicated three genetically distinct units—the Atlantic, eastern Gulf, and western Gulf—that align with regional stocks and suggest regional philopatry by males and females. Heterogeneity at loci putatively under selection, associated with temperature and salinity, was observed among sites within Gulf units, suggesting local adaptation. Furthermore, five pairs of siblings were identified in the same site across timescales corresponding with female reproductive cycles. This indicates that females re‐used a site for parturition, which has the potential to facilitate the sorting of adaptive variation among neighbouring sites. The results demonstrate differential impacts of microevolutionary forces at varying spatial scales and highlight the importance of conserving essential habitats to maintain sources of adaptive variation that may buffer species against environmental change.

Integrated field, model, and theoretical advances inform a predictive understanding of transport and transformation in the critical zone - Joel Singley; Martin Briggs; Beth Hoagland; Rachel Lauer; Jessie Meeks; Aaron B. Regberg; David M. Rey; Kenny Swift Bird; Adam S. Ward (Journal of Hydrology, 2023)

4D electrical resistivity to monitor unstable slopes in mountainous tropical regions: an example from Munnar, India - Arnaud Watlet; Hemalatha Thirugnanam; Balmukund Singh; Nitin Kumar M.; Deepak Brahmanandan; Cornelia Inauen; Russell Swift; Phil Meldrum; Sebastian Uhlemann; Paul Wilkinson; Jonathan Chambers; Maneesha Vinodini Ramesh (Landslides, 2023)
The number of large landslides in India has risen in the recent years, due to an increased occurrence of extreme monsoon rainfall events. There is an urgent need to improve our understanding of moisture-induced landslide dynamics, which vary both spatially and temporally. Geophysical methods provide integrated tools to monitor subsurface hydrological processes in unstable slopes at high spatial resolution. They are complementary to more conventional approaches using networks of point sensors, which can provide high temporal resolution information but are severely limited in terms of spatial resolution. Here, we present and discuss data from an electrical resistivity tomography monitoring system—called PRIME—deployed at the Amrita Landslide Early Warning System (Amrita-LEWS) site located in Munnar in the Western Ghats (Kerala, India). The system monitors changes in electrical resistivity in the subsurface of a landslide-prone slope that directly threatens a local community. The monitoring system provides a 4D resistivity model informing on the moisture dynamics in the subsurface of the slope. Results from a 10-month period spanning from pre-monsoon to the end of the monsoon season 2019 are presented and discussed with regard to the spatial variation of soil moisture. The temporal changes in resistivity within the slope are further investigated through the use of time-series clustering and compared to weather and subsurface pore water pressure data. This study sheds new light on the hydrological processes occurring in the shallow subsurface during the monsoon and potentially leading to slope failure. This geophysical approach aims at better understanding and forecasting slope failure to reduce the risk for the local community, thereby providing a powerful tool to be included in local landslide early warning systems.

Perinatal oxycodone exposure causes long-term sex-dependent changes in weight trajectory and sensory processing in adult mice - Elena Minakova; Marwa O. Mikati; Manish K. Madasu; Sineadh M. Conway; Justin W. Baldwin; Raylynn G. Swift; Katherine B. McCullough; Joseph D. Dougherty; Susan E. Maloney; Ream Al-Hasani (Psychopharmacology, 2022)

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Acute cardiac autonomic and haemodynamic responses to leg and arm isometric exercise - Harry T. Swift; Jamie M. O’Driscoll; Damian D. Coleman; Anthony De Caux; Jonathan D. Wiles (European Journal of Applied Physiology, 2022)

An inpatient human laboratory study assessing the safety and tolerability, pharmacokinetics, and biobehavioral effect of GET 73 when co-administered with alcohol in individuals with alcohol use disorder - Carolina L. Haass-Koffler; Roberta Perciballi; Molly Magill; Antonella Loche; Roberto Cacciaglia; Lorenzo Leggio; Robert M. Swift (Psychopharmacology, 2022)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Fungal communities living within leaves of native Hawaiian dicots are structured by landscape‐scale variables as well as by host plants - John L. Darcy; Sean O. I. Swift; Gerald M. Cobian; Geoffrey L. Zahn; Brian A. Perry; Anthony S. Amend (Molecular Ecology, 2020)
A phylogenetically diverse array of fungi live within healthy leaf tissue of dicotyledonous plants. Many studies have examined these endophytes within a single plant species and/or at small spatial scales, but landscape‐scale variables that determine their community composition are not well understood, either across geographic space, across climatic conditions, or in the context of host plant phylogeny. Here, we evaluate the contributions of these variables to endophyte beta diversity using a survey of foliar endophytic fungi in native Hawaiian dicots sampled across the Hawaiian archipelago. We used Illumina technology to sequence fungal ITS1 amplicons to characterize foliar endophyte communities across five islands and 80 host plant genera. We found that communities of foliar endophytic fungi showed strong geographic structuring between distances of 7 and 36 km. Endophyte community structure was most strongly associated with host plant phylogeny and evapotranspiration, and was also significantly associated with NDVI, elevation and solar radiation. Additionally, our bipartite network analysis revealed that the five islands we sampled each harboured significantly specialized endophyte communities. These results demonstrate how the interaction of factors at large and small spatial and phylogenetic scales shapes fungal symbiont communities.

Noradrenergic targets for the treatment of alcohol use disorder - Carolina L. Haass-Koffler; Robert M. Swift; Lorenzo Leggio (Psychopharmacology, 2018)

Pharmacogenetics of stimulant abuse liability: association of CDH13 variant with amphetamine response in a racially-heterogeneous sample of healthy young adults - Adam M. Leventhal; Matthew G. Kirkpatrick; Mollie S. Pester; John E. McGeary; Robert M. Swift; Steve Sussman; Christopher W. Kahler (Psychopharmacology, 2017)

The Influence of Host Plant Volatiles on the Attraction of Longhorn Beetles to Pheromones - R. Maxwell Collignon; Ian P. Swift; Yunfan Zou; J. Steven McElfresh; Lawrence M. Hanks; Jocelyn G. Millar (Journal of Chemical Ecology, 2016)

Emotional traits predict individual differences in amphetamine-induced positive mood in healthy volunteers - Matthew G. Kirkpatrick; Nicholas I. Goldenson; Nahel Kapadia; Christopher W. Kahler; Harriet de Wit; Robert M. Swift; John E. McGeary; Steve Sussman; Adam M. Leventhal (Psychopharmacology, 2016)

Functional response of the isolated, perfused normoxic heart to pyruvate dehydrogenase activation by dichloroacetate and pyruvate - Rafael Jaimes; Sarah Kuzmiak-Glancy; Daina M. Brooks; Luther M. Swift; Nikki G. Posnack; Matthew W. Kay (Pflügers Archiv - European Journal of Physiology, 2016)

Natural product extracts of the Canadian prairie plant, Thermopsis rhombifolia, have anti-cancer activity in phenotypic cell-based assays - Sophie Kernéis; Lucy H. Swift; Cody W. Lewis; Céline Bruyère; Nassima Oumata; Pierre Colas; Sandrine Ruchaud; John Bain; Roy M. Golsteyn (Natural Product Research, 2015)

Erratum to: A preliminary double-blind, placebo-controlled randomized study of baclofen effects in alcoholic smokers - Lorenzo Leggio; William H. Zywiak; Steven M. Edwards; Jennifer W. Tidey; Robert M. Swift; George A. Kenna (Psychopharmacology, 2015)

A preliminary double-blind, placebo-controlled randomized study of baclofen effects in alcoholic smokers - Lorenzo Leggio; William H. Zywiak; Steven M. Edwards; Jennifer W. Tidey; Robert M. Swift; George A. Kenna (Psychopharmacology, 2015)

Properties of blebbistatin for cardiac optical mapping and other imaging applications - Luther M. Swift; Huda Asfour; Nikki G. Posnack; Ara Arutunyan; Matthew W. Kay; Narine Sarvazyan (Pflügers Archiv - European Journal of Physiology, 2012)

The Relationship of Appetitive, Reproductive and Posterior Pituitary Hormones to Alcoholism and Craving in Humans - George A. Kenna; Robert M. Swift; Thomas Hillemacher; Lorenzo Leggio (Neuropsychology Review, 2012)

2,3-Hexanediols as Sex Attractants and a Female-produced Sex Pheromone for Cerambycid Beetles in the Prionine Genus Tragosoma - Ann M. Ray; James D. Barbour; J. Steven McElfresh; Jardel A. Moreira; Ian Swift; Ian M. Wright; Alenka Žunič; Robert F. Mitchell; Elizabeth E. Graham; Ronald L. Alten; Jocelyn G. Millar; Lawrence M. Hanks (Journal of Chemical Ecology, 2012)

Adoption of variable rate fertiliser application in the Australian grains industry: status, issues and prospects - M. J. Robertson; R. S. Llewellyn; R. Mandel; R. Lawes; R. G. V. Bramley; L. Swift; N. Metz; C. O’Callaghan (Precision Agriculture, 2012)

(R)-Desmolactone, A Female-produced Sex Pheromone Component of the Cerambycid Beetle Desmocerus californicus californicus (subfamily Lepturinae) - Ann M. Ray; Ian P. Swift; J. Steven McElfresh; Ronald L. Alten; Jocelyn G. Millar (Journal of Chemical Ecology, 2012)

A novel molecular mechanism to explain biotin-unresponsive holocarboxylase synthetase deficiency - Lungisa Mayende; Rachel D. Swift; Lisa M. Bailey; Tatiana P. Soares da Costa; John C. Wallace; Grant W. Booker; Steven W. Polyak (Journal of Molecular Medicine, 2012)

Effects of contingency management and bupropion on cigarette smoking in smokers with schizophrenia - Jennifer W. Tidey; Damaris J. Rohsenow; Gary B. Kaplan; Robert M. Swift; Netesha Reid (Psychopharmacology, 2011)

A combined visual and acoustic estimate of 2008 abundance, and change in abundance since 1997, for the vaquita, Phocoena sinus - Tim Gerrodette; Barbara L. Taylor; René Swift; Shannon Rankin; Armando M. Jaramillo‐Legorreta; Lorenzo Rojas‐Bracho (Marine Mammal Science, 2011)
A line‐transect survey for the critically endangered vaquita, Phocoena sinus , was carried out in October–November 2008, in the northern Gulf of California, Mexico. Areas with deeper water were sampled visually from a large research vessel, while shallow water areas were covered by a sailboat towing an acoustic array. Total vaquita abundance in 2008 was estimated to be 245 animals (CV = 73%, 95% CI 68–884). The 2008 estimate was 57% lower than the 1997 estimate, an average rate of decline of 7.6%/yr. Bayesian analyses found an 89% probability of decline in total population size during the 11 yr period, and a 100% probability of decline in the central part of the range. Acoustic detections were assumed to represent porpoises with an average group size of 1.9, the same as visual sightings. Based on simultaneous visual and acoustic data in a calibration area, the probability of detecting vaquitas acoustically on the trackline was estimated to be 0.41 (CV = 108%). The Refuge Area for the Protection of the Vaquita, where gill net fishing is currently banned, contained approximately 50% of the population. While animals move in and out of the Refuge Area, on average half of the population remains exposed to bycatch in artisanal gill nets.

Feeding behavior of the ctenophore Thalassocalyce inconstans: revision of anatomy of the order Thalassocalycida - Holly F. Swift; William M. Hamner; Bruce H. Robison; Laurence P. Madin (Marine Biology, 2009)

Typologies of Alcohol Dependence. From Jellinek to Genetics and Beyond - Lorenzo Leggio; George A. Kenna; Miriam Fenton; Erica Bonenfant; Robert M. Swift (Neuropsychology Review, 2009)

Male-Produced Aggregation Pheromone of the Cerambycid Beetle Rosalia funebris - Ann M. Ray; Jocelyn G. Millar; J. Steven McElfresh; Ian P. Swift; James D. Barbour; Lawrence M. Hanks (Journal of Chemical Ecology, 2009)

Observations of pigment and particle distributions in the western North Atlantic from an autonomous float and ocean color satellite - E. Boss; D. Swift; L. Taylor; P. Brickley; R. Zaneveld; S. Riser; M. J. Perry; P. G. Strutton (Limnology and Oceanography, 2008)
Profiling floats with optical sensors can provide important complementary data to satellite ocean color determinations by providing information about the vertical structure of ocean waters, as well as surface waters obscured by clouds. Here we demonstrate this ability by pairing satellite ocean color data with records from a profiling float that obtained continuous, high‐quality optical data for 3 yr in the North Atlantic Ocean. Good agreement was found between satellite and float data, and the relationship between satellite chlorophyll and floatderived particulate backscattering was consistent with previously published data. Upper ocean biogeochemical dynamics were evidenced in float measurements, which displayed strong seasonal patterns associated with phytoplankton blooms, and depth and seasonal patterns associated with an increase in pigmentation per particle at low light. Surface optical variables had shorter decorrelation timescales than did physical variables (unlike at low latitudes), suggesting that biogeochemical rather than physical processes controlled much of the observed variability. After 2.25 yr in the subpolar North Atlantic between Newfoundland and Greenland, the float crossed the North Atlantic Current to warmer waters, where it sampled an unusual eddy for 3 months. This anticyclonic feature contained elevated particulate material from surface to 1000‐m depth and was the only such event in the float's record. This eddy was associated with weakly elevated surface pigment and backscattering, but depthintegrated backscattering was similar to that previously observed during spring blooms. Such seldom‐observed eddies, if frequent, are likely to make an important contribution to the delivery of particles to depth.

Pharmacological effects of naltrexone and intravenous alcohol on craving for cigarettes among light smokers: a pilot study - Lara A. Ray; Robert Miranda; Christopher W. Kahler; Adam M. Leventhal; Peter M. Monti; Robert Swift; Kent E. Hutchison (Psychopharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

Differences in sensory ecology contribute to resource partitioning in the bats Myotis bechsteinii and Myotis nattereri (Chiroptera: Vespertilionidae) - Björn M. Siemers; Susan M. Swift (Behavioral Ecology and Sociobiology, 2006)

Underground excavations in rock salt - G. M. Swift; D. J. Reddish (Geotechnical and Geological Engineering, 2005)

Olanzapine attenuates cue-elicited craving for tobacco - Kent E. Hutchison; Marie-Christine Rutter; Raymond Niaura; Robert M. Swift; Wallace B. Pickworth; Laura Sobik (Psychopharmacology, 2003)

Comparative phylogeography of sympatric sister species, Clevelandia ios and Eucyclogobius newberryi (Teleostei, Gobiidae), across the California Transition Zone - M. N Dawson; K. D. Louie; M. Barlow; D. K. Jacobs; C. C. Swift (Molecular Ecology, 2002)
It is paradigmatic in marine species that greater dispersal ability often, but not always, results in greater gene flow and less population structure. Some of the exceptions may be attributable to studies confounded by comparison of species with dissimilar evolutionary histories, i.e. co‐occurring species that are not closely related or species that are closely related but allopatric. Investigation of sympatric sister species, in contrast, should allow differences in phylogeographic structure to be attributed reliably to recently derived differences in dispersal ability. Here, using mitochondrial DNA control region sequence, we first confirm that Clevelandia ios and Eucyclogobius newberryi are sympatric sister taxa, then demonstrate considerably shallower phylogeographic structure in C. ios than in E. newberryi . This shallower phylogeographic structure is consistent with the higher dispersal ability of C. ios , which most likely results from the interaction of habitat and life‐history differences between the species. We suggest that the paradigm will be investigated most rigorously by similar studies of other sympatric sister species, appended by thorough ecological studies, and by extending this sister‐taxon approach to comparative phylogeographic studies of monophyletic clades of sympatric species.

Effect of luminance level on electro-encephalogram alpha-wave synchronisation - A. M. Maher; L. Kirkup; P. Swift; D. Martin; A. Searle; Y. Tran; A. Craig (Medical & Biological Engineering & Computing, 2001)

Olanzapine reduces urge to drink after drinking cues and a priming dose of alcohol - Kent E. Hutchison; Robert Swift; Damaris J. Rohsenow; Peter M. Monti; Dena Davidson; Alissa Almeida (Psychopharmacology, 2001)

Short-pulse pump-and-probe technique for airborne laser assessment of Photosystem II photochemical characteristics - Alexander M. Chekalyuk; Frank E. Hoge; Charles W. Wright; Robert N. Swift (Photosynthesis Research, 2000)

Airborne test of laser pump-and-probe technique for assessment of phytoplankton photochemical characteristics - Alexander M. Chekalyuk; Frank E. Hoge; Charles W. Wright; Robert N. Swift; James K. Yungel (Photosynthesis Research, 2000)

Alley cropping of maize with calliandra and leucaena in the subhumid highlands of Kenya: Part 2. Biomass decomposition, N mineralization, and N uptake by maize - D. N. Mugendi; P. K. R. Nair; J. N. Mugwe; M. K. O'Neill; M. J. Swift; P. Woomer (Agroforestry Systems, 1999)

Effects of naltrexone with nicotine replacement on smoking cue reactivity: preliminary results - K. E. Hutchison; Peter M. Monti; Damaris J. Rohsenow; Robert M. Swift; Suzanne M. Colby; Maryann Gnys; Raymond S. Niaura; Alan D. Sirota (Psychopharmacology, 1999)

Global change, soil biodiversity, and nitrogen cycling in terrestrial ecosystems: three case studies - M. J. SWIFT; O. ANDRÉN; L. BRUSSAARD; M. BRIONES; M. ‐M. COUTEAUX; K. EKSCHMITT; A. KJOLLER; P. LOISEAU; P. SMITH (Global Change Biology, 1998)
The relative contribution of different soil organism groups to nutrient cycling has been quantified for a number of ecosystems. Some functions, particularly within the N‐cycle, are carried out by very specific organisms. Others, including those of decomposition and nutrient release from organic inputs are, however, mediated by a diverse group of bacteria, protozoa, fungi and invertebrate animals. Many authors have hypothesized that there is a high degree of equivalence and flexibility in function within this decomposer community and thence a substantial extent of redundancy in species richness and resilience in functional capacity. Three case studies are presented to examine the relationship between soil biodiversity and nitrogen cycling under global change in ecosystem types from three latitudes, i.e. tundra, temperate grassland and tropical rainforest. In all three ecosystems evidence exists for the potential impact of global change factors (temperature change, CO 2 enrichment, land‐use‐change) on the composition and diversity of the soil community as well as on various aspects of the nitrogen and other cycles. There is, however, very little unequivocal evidence of direct causal linkage between species richness and nutrient cycling efficiency. Most of the changes detected are shifts in the influence of major functional groups of the soil biota (e.g. between microflora and fauna in decomposition). There seem to be few data, however, from which to judge the significance of changes in diversity within functional groups. Nonetheless the soil biota are hypothesized to be a sensitive link between plant detritus and the availability of nutrients to plant uptake. Any factors affecting the quantity or quality of plant detritus is likely to change this link. Rigorous experimentation on the relationships between soil species richness and the regulation or resilience of nutrient cycles under global change thus remains a high priority.

Potentials of Millettia thonningii and Pterocarpus santalinoides for alley cropping in humid lowlands of West Africa - E. A. Egbe; D. O. Ladipo; L. C. Nwoboshi; M. J. Swift (Agroforestry Systems, 1998)

Use of the SCUAF model to simulate natural miombo woodland and maize monoculture ecosystems in Zimbabwe - S. J. Vermeulen; P. Woomer; B. M. Campbell; W. Kamukondiwa; M. J. Swift; P. G. H. Frost; C. Chivaura; H. K. Murwira; F. Mutambanengwe; P. Nyathi (Agroforestry Systems, 1993)